Translational optical coherence elastography for assessment of systemic sclerosis. Issue 12 (8th August 2019) - Liu, Chih‐Hao; Assassi, Shervin; Theodore, Sam; Smith, Christopher; Schill, Alexander; Singh, Manmohan; Aglyamov, Salavat; Mohan, Chandra; Larin, Kirill V.
Abstract: Systemic sclerosis (SSc‐scleroderma) is an autoimmune disorder with high mortality rate that results in excessive accumulation of collagen in the skin and internal organs. Currently, the modified Rodnan Skin Score (mRSS) is the gold standard for evaluating the dermal thickening due to SSc. However, mRSS has noticeable inter‐ and intra‐observer variabilities as quantified by the interclass correlation coefficient (ICC: 0.6‐0.75). In this work, optical coherence elastography (OCE) combined with structural optical coherence tomography (OCT) image analysis was used to assess skin thickness in 12 SSc patients and healthy volunteers. Inter‐ (ICC: 0.62‐0.99) and intra‐observer (ICC > 0.90) assessment of OCT/OCE showed excellent reliability. Clinical assessments, including histologically assessed dermal thickness (DT), mRSS, and site‐specific mRSS (SMRSS) were also performed for further validation. The OCE and OCT results from the forearm demonstrated the highest correlation (OCE: 0.78, OCT: 0.65) with SMRSS. Importantly, OCE and OCT had stronger correlations with the histological DT (OCT: r = .78 and OCE: r = .74) than SMRSS ( r = .57), indicating the OCT/OCE could outperform semi‐quantitative clinical assessments such as SMRSS. Overall, these results demonstrate that OCT/OCE could be useful for rapid, noninvasive and objective assessments of SSc onset and monitoring skin disease progression and treatment response. Abstract : Systemic sclerosis (SSc) is an autoimmune disorder with high mortality rate that results in excessive accumulation of collagen in the skin and internal organs. To detect the disease severity, air‐pulse‐based optical coherence elastography (OCE) combined with structural analysis enables excellent reliability and stronger correlation with dermal thickness as compared to the site‐specific skin score assessed by an experienced physician. The results indicate that optical coherence tomography/OCE could be useful for rapid, noninvasive and objective assessments of SSc onset and progression and for therapy evaluation.